SIMULASI GATEWAY LOAD BALANCE PROTOCOL MENGGUNAKAN METODE WEIGHT - Djoko Suprijatmono; Iwan Hernawan; Septa Setiadi (Bina Teknika, 2018)
To support qualified IT operations, recently many companies have hired more than 1 (one) communication link as a redundancy and to improve High Availability or the availability of their network systems. One method to improve high availability of multi router networks (links) is to use Gateway Load Balance Protocol (GLBP) which is a protocol that works on OSI layer 3. Where the GLBP function is to divide the traffic load and as a failover function when one router / link is damaged. Gateway Load Balancing Protocol (GLBP) itself is born from the concept of load balancing, a concept that is useful for dividing / balancing loads or loads on multiple links to the same remote network. That way the network link will not be disturbed if there is damage caused by one of the routers.This thesis describes the concept of GLBP by using the weight method where network simulation tools use GNS3 software. The results obtained from the simulation with GLBP weight method sharing the router data load is determined by the weight value given to each router. Where Comparison of Weight Values given to the Router will determine the number of data packets transmitted to the router.